Cardiac biomarkers comparison between acute myocarditis/myopericarditis and multisystem inflammatory syndrome in children - Duman, Derya; Karpuz, Derya (The European Research Journal, 2023)
Objectives: Acute myocarditis/myopericarditis is a heterogeneous disorder of unknown origin, the viral etiology leading the first row. There could be also myocardial involvement in multisystem inflammatory syndrome in children (MIS-C). In this study, we aimed to investigate cardiac biomarkers of acute myocarditis/myopericarditis and MIS-C and to compare these parameters between the two diseases. Methods: Patients who are diagnosed with MIS-C, isolated viral myocarditis/myopericarditis at a university hospital from October 2021 to March 2023 are included in this study. Results: There were 38 MIS-C patients and 53 patients with myocarditis/myopericarditis. The mean age was 141.2 ± 38.2 months (4 to 18 years old) in MISC, and 145.8 ± 52.1 months (7 to 18 years old) in myocarditis/myopericarditis. Median troponin I level was 145 ng/L in MIS-C patients and it was 901 ng/L in myocarditis/myopericarditis patients. Creatinine kinase-myocardial band (CK-MB) median was 2.25 ng/mL (0.6-6.3) versus 6.7 ng/mL in MIS-C and myocarditis/myopericarditis, respectively. Pro Brain natriuretic peptide (Pro-BNP) median level was 2714.5 pg/mL (